Penggunaan Alih Kode dan Campur Kode Dalam Video di Kanal Youtube Yannie Kim: Kajian Sosiolinguistik - Malau, Apfia Novrisa Dwina; Samsudin, Didin; Azizah, Asma (Syntax Literate, 2025)
This study discusses the phenomenon of code switching and code mixing in YouTube videos of Yannie Kim, a YouTuber who lives in an Indonesian-Korean bilingual family. Code switching and code mixing are common phenomena in bilingual communities, where individuals use more than one language in one conversation. This study aims to identify the types of code switching and code mixing used in video interactions on Yannie Kim's YouTube channel, as well as to understand the factors that influence their use. The method used is descriptive qualitative, with data collection techniques in the form of watching and taking notes on selected videos from Yannie Kim's YouTube channel. Data were analyzed based on the types of situational code switching, and metaphorical code switching and types of code mixing in the form of words, phrases, and clauses. The analysis was carried out by referring to sociolinguistic theory. The results of the study show that situational and metaphorical code switching occur flexibly in Yannie Kim's family conversations, often triggered by factors such as changes in audience, emotional expression, or communicative goals. Meanwhile, code mixing is used more to clarify messages or increase emotional depth, reflecting a modern communication style. These two phenomena play an important role in accommodating cultural and linguistic differences in bilingual families and communities. This research is expected to contribute to sociolinguistic studies, especially related to the use of code switching and code mixing in the context of social media and bilingual family life. This research is also expected to enrich the understanding of language dynamics in multicultural communities and how language is used as a means of cross-cultural communication.